The RING Finger Protein NtRCP1 Is Involved in the Floral Transition in Tobacco (Nicotiana tabacum). Issue 6 (20th June 2015) - Wang, Hai-Yun; Yu, Yi; Sun, Yong-Duo; Han, Li-Bo; Wu, Xiao-Min; Wu, Jia-He; Xia, Gui-Xian; Liu, Guo-Qin
Abstract The transition from the vegetative phase to the reproductive phase is a major developmental process in flowering plants. The underlying mechanism controlling this cellular process remains a research focus in the field of plant molecular biology. In the present work, we identified a gene encoding the C3H2C3-type RING finger protein NtRCP1 from tobacco BY-2 cells. Enzymatic analysis demonstrated that NtRCP1 is a functional E3 ubiquitin ligase. In tobacco plants, expression level of NtRCP1 was higher in the reproductive shoot apices than in the vegetative ones. NtRCP1-overexpressing plants underwent a more rapid transition from the vegetative to the reproductive phase and flowered markedly earlier than the wild-type control. Histological analysis revealed that the shoot apical meristem of NtRCP1-overexpressing plants initiated inflorescence primordia precociously compared to the wild-type plant due to accelerated cell division. Overexpression of NtRCP1 in BY-2 suspension cells promoted cell division, which was a consequence of the shortened G2 phase in the cell cycle. Together, our data suggest that NtRCP1 may act as a regulator of the phase transition, possibly through its role in cell cycle regulation, during vegetative/reproductive development in tobacco plant.